Efektivitas Model Games Based Learning Berbasis Wordwall Terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika Kelas VII SMPN 4 Sutera - Alifa, Riqhel; Yeni J, Fetri; Amsal, Mutiara Felicita; Anugrah, Septryan (Indo-MathEdu Intellectuals Journal, 2024)
The problem found in the field is the low learning outcomes of students in informatics subjects caused by the application of informatics models that do not vary which makes the learning atmosphere seem boring, less attractive to students so that learning has not been achieved optimally. This study aims to determine the effectiveness of the wordwall-based games-based learning model on student learning outcomes in Informatics subjects at SMP 4 Sutera. The type of research used by the researcher is a quasi experiment The sampling technique used is a cluster random sampling technique. Data collection techniques use tests. Data analyzed with the Mann Whitney test. The results of the study showed that after conducting data analysis tests and hypotheses using the wilcoxon and mann whitney tests, the Asymp value was obtained. Sign (2-tailed) < 0.05 then Ho is rejected, and Ha is accepted. After using the games-based learning model, it was higher and experienced a significant increase compared to using the conventional learning model. Therefore, the games based learning model can be declared effective and able to improve student learning outcomes in Informatics class VII SMPN 4 Sutera